A Study of Calcination and Carbonation of Cockle Shell - Rashidi, Nor Adilla (2011)
Calcium oxide (CaO) as carbon dioxide (CO2) adsorbent at the elevated temperature has been very well-received thus far. The CaO can be synthesized from natural calcium carbonate (CaCO3) sources through the reversible calcination-carbonation process. In the study, cockle shell has been selected as CaO precursors. The objectives of the study are to investigate the performance of calcination and carbonation with respect to different temperature, heating rate, particle size and the duration time. Overall, better performance is shown at the calcination temperature of 850oC for 40 minutes, heating rate of 20oC/min, particle size of < 0.125mm and the carbonation temperature is at 650oC. The synthesized materials have been characterized by nitrogen physisorption and surface morphology analysis. The effectiveness of the synthesized cockle shell in capturing CO2 (0.72 kg CO2/kg adsorbent) which is comparable to the commercialized adsorbent (0.60 kg CO2/kg adsorbent) makes them as the most promising materials for CO2 capture.